Electrochemical sensors for β-adrenoceptor agonist isoprenaline analysis in human urine and serum samples using manganese cobalt oxide-modified glassy carbon electrode. (5th May 2021) - Manjula, Natesan; Chen, Shen-Ming
Abstract : Schematic illustration for the synthesis of the MCO nanosphere and modification with GCE towards the electrochemical determination of isoprenaline. Abstract : We demonstrated a simple and more accurate electrochemical sensor for isoprenaline (ISPT) analysis in pharmaceutical substances based on manganese cobalt oxide (MnCo2 O4 ) modified with a glassy carbon electrode (MCO/GCE). The nanomaterial was synthesized via coprecipitation approach and characterized with various methods, including FTIR, XRD, HRTEM, FESEM, and XPS. Different experimental factors concerning the electrochemical activity of the fabricated electrode have been optimized through varying pH, loading quantity, and scan rates. The present sensor displayed powerful and consistent electron mediating activity accompanied by well-separated oxidation peaks with low overpotential activation towards ISPT. MCO/GCE was effectively used for the determination of ISPT in the concentration range from 0.2 to 121 μM with the sensitivity of 10.01 μA μM −1 cm −2, and the detection limit was 0.005 μM by differential pulse voltammetry. Surprisingly, the suggested electrode shows good reproducibility, repeatability, selectivity, and stability. Standard addition findings revealed the promising potential of MCO/GCE as an effective catalyst for the determination of ISPT in human urine and serum samples with acceptable recovery values attained at 99 to 101.2%.